Association of Complement Receptor 2 Gene Polymorphisms with Susceptibility to Osteonecrosis of the Femoral Head in Systemic Lupus Erythematosus. (30th June 2016) - Kim, Tae-Ho; Bae, Sang-Cheol; Lee, Sang-Han; Kim, Shin-Yoon; Baek, Seung-Hoon
Abstract : Osteonecrosis of the femoral head (ONFH) is a complex and multifactorial disease that is influenced by a number of genetic factors in addition to environmental factors. Some autoimmune disorders, including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and inflammatory bowel disease (IBD), are associated with the development of ONFH. Complement receptor type 2 ( CR2 ) is membrane glycoprotein which binds C3 degradation products generated during complement activation. CR2 has many important functions in normal immunity and is assumed to play a role in the development of autoimmune disease. We investigated whether CR2 gene polymorphisms are associated with risk of ONFH in SLE patients. Eight polymorphisms in the CR2 gene were genotyped using TaqMan ™ assays in 150 SLE patients and 50 ONFH in SLE patients (SLE_ONFH). The association analysis of genotyped SNPs and haplotypes was performed with ONFH. It was found that three SNPs, rs3813946 in 5′-UTR (untranslated region), rs311306 in intron 1, and rs17615 in exon 10 (nonsynonymous SNP; G/A, Ser639Asn) of the CR2 gene, were associated with an increased risk of ONFH under recessive model (P values; 0.004~0.016). Haplotypes were also associated with an increased risk (OR; 3.73~) of ONFH in SLE patients. These findings may provide evidences that CR2 contributes to human ONFH susceptibility in Korean SLE patients.